The Impact of Leg Press Training and Squat Training on the Weapon Attack Ability of Fencing Athletes in South Sulawesi - Ihsan, Andi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to determine the effect of leg press training and squat training on the ability of degen weapon attacks in South Sulawesi athletes' fencing. The study employed a quasi-experimental research method, utilizing a two-group pre- and post-test design on a sample of 20 individuals. The matched ordinal pairing technique ranked the attack ability based on the pre-test results, resulting in the formation of two treatment groups. Each group consisted of 10 people using leg press exercises, and one group used squat exercises. We carried out the treatment for 16 meetings, training three times a week, performing 3–4 sets and 10–14 repetitions, and loading each sample according to their individual abilities. Based on the results of the data analysis, it was found that leg press training had a significant effect of -3,959 > α. 0.05 on the attack ability of degen weapons in South Sulawesi athletes' fencing. Squat training has a significant effect of -8,200 > α 0.05 on the ability of degen weapon attacks in South Sulawesi athletes' fencing. The effect of squat training is more effective when compared to leg press training in increasing the ability of degen weapon attacks in South Sulawesi athletes' fencing. Squat training is more effective because the movement characteristics of squat training are closer to the characteristics of attack movements in fencing. The results of this study recommend that coaches and athletes, to improve their dominant physical components to increase their ability to attack weapons in fencing, should choose leg press and squat exercises.